New herb gall wasps from Iran (Hymenoptera: Cynipidae) - Tavakoli, Majid; Stone, Graham N.; Pujade-Villar, Juli; Melika, George (Zootaxa, 2022)
Five new gall wasp species, Aulacidea koeiana Melika, Tavakoli & Stone, sp. nov., A. lorestanica Melika, Tavakoli & Stone, sp. nov., A. piroziae Melika, Stone & Pujade-Villar, sp. nov., Phanacis strigosa Melika, Stone & Tavakoli, sp. nov., P. tavakolii Melika, Stone & Pujade-Villar, sp. nov. are described from Lorestan, Iran. Descriptions, diagnoses, plus information on biology and host associations are given for all new species, and we provide the first description of the male of Isocolus beheni Melika & Karimpour, 2008.